The Impact of trust and fairness by financial services on consumer satisfaction. - Ranganathan, Manassa (2019)
This work analyses the importance and impact that trust and fairness in financial services sector have on consumer satisfaction. Ethics is a widely researched topic and the for all business activities. How ethical a business is impacts the satisfaction as well the dissatisfaction in consumers. And, the financial services sector is run solely on the satisfaction of the consumers. Trust and fairness are formed as an effect of interpersonal relationships between a service provider and their consumers. Loyalty is cultivated only when trust is built. And trust is built only when consumers feel that they are being treated fairly. In this paper, the impact of trust in financial service analysed using the questionnaire method. The purpose of the survey was used to show the importance of trust and to ascertain what generates, retains and affects the trust in consumers. Though the survey, this paper majorly establishes that apart from service provider–consumer relationship, which is highlighted by many researches, Trust it is generated through various aspects other like brand name of the financial service provider, image of the provider, how they treat their employees and how much the providers value the privacy of the consumers. Thus, this survey establishes that even though many consumers do not have a high knowledge about financial services, they also have their own ethical perspectives and expectations about how the financial services industry should function. The growth and longevity of this industry solely depends on safeguarding the consumer trust and improving their satisfaction.